Review Borzyak E. I. Human anatomy. Photographic Atlas. The 3 volumes / E. I Borzyak, G. von Hagens, I. N. Putalova. – Moscow: GEOTARMedia, 2014. - journal "Morphologia", Editorial office of (Морфологія / Morphologia / Morfologìâ, 2015)
In the proposed atlas are not colorful schemes and drawings of the structure of the human body, mostly far from reality, but photographs of natural anatomical preparations that show the true structure of the human body.